Assessment of the Zimbabwe Public Finance Management System for Investment Lending Projects - World Bank Group (World Bank, Washington, DC, 2016)
This study was undertaken under the leadership of the Ministry of Finance and Economic Development (MOFED) to assess fiduciary risks in using country financial management (FM) systems in full, or in part, for implementing Donor and Bank-financed investment projects in Zimbabwe and to identify risk mitigation measures required for such use. Fiduciary risk is the risk that Bank funds (or donor funds) will not be used for their intended purposes or that they will be used without due attention to economy and efficiency. In projects using country FM systems, Bank funds are potentially commingled with the country’s own funds; therefore, a fiduciary risk assessment also needs to consider broader country PFM risks that could affect the fiduciary risk. This assessment uses a risk-based approach consistent with the interim guidance note issued by the FM Sector Board in 2009, entitled ‘assessment of fiduciary risks in the use of country FM systems in bank-financed investment projects’; and supplemented by the framework methodology for channeling investment lending projects through country financial management systems and the approach used for regular FM assessments. The risk-based approach provides a ranking of the fiduciary risks to be managed as high, substantial, moderate, or low. The decision to use country systems for a specific project then rests with the project's task team, guided by the country management team, after taking into account this fiduciary risk assessment and other factors such as the nature and complexity of the project and an assessment of implementing entities.